CONSIDERATIONS REGARDING THE CONDITION, AS A MODALITY OF THE LEGAL ACT - Valentin COCEAN (Challenges of the Knowledge Society)
The provisions of the new civil code did not bring significant changes to the matter of modalities, instead they clarified some aspects, which in the past, due to lack of legislative clarification, could spark controversy. Nevertheless, for an accurate understanding of the condition as a modality of the legal act an analysis is still necessary, particularly regarding the role of the parties’ will and their conduct in relation to the condition included in the contract.